(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This paper discusses the plight of poor, middle class problems which existed in 20th century post modern world. Sri Sri’s literature unveils the Indian socio-political circumstances, its impact on the common people. Every one has life, it is interrelated with social history. Inequalities, Aristocratic class attitude, oppressing the poor people existed in this world. Sri sri understood history, culture of India. He stood behind poverty stricken people , backed up and coined Nenu Saitham word. Sri Sri wished to create egalitarian society in India. His poems reveal that exploitation of labour, capitalism impact, small bureaucrat’s life. His appeal to the people is not to fall for investor’s magic. Government should be responsible towards the welfare of poor people, petty peasants but not economic reforms. In the modern world, investment is showing ugly face in the name of development, talent, genius migration, beauty. In my view Sri sri literature helps the modern readers a lot to come out of the materialistic life.